RETIREMENT CHALLENGES AND TRANSITIONS: A QUALITATIVE EXPLORATION OF RETIREES’ EXPERIENCES - Dzurizah Ibrahim; Jalihah Md Shah; Amirah Saliha Godfrey (Journal of Islamic, Social, Economics and Development, 2024)
Retirement presents complex challenges for public sector retirees, particularly those in Malaysia's B40 demographic. Financial vulnerability, often stemming from sole reliance on pension funds, looms large, especially with retirement age typically set at 60. As Malaysia trends towards an ageing society by 2030, comprehending retirement complexities is paramount. This study, conducted in Ranau, Sabah, focuses on B40 retirees, aiming to reveal financial implications and broader challenges during the retirement transition. By informing tailored policies and interventions, the research endeavours to uplift the well-being of B40 retirees in the public sector. Through semi-structured interviews, six male B40 retirees shared their retirement journeys. Thematic analysis unveiled recurring themes, shedding light on retirees' challenges and experiences, and fostering a nuanced understanding of retirement dynamics. Findings highlight the profound impact of income inadequacy, empty nest syndrome, lifestyle adjustments, and health concerns on retirees' well-being and quality of life. Employing a qualitative approach, the study enriches our comprehension of retirement experiences by capturing retirees' subjective perspectives and interpretations. By prioritizing retirees' financial security, social support networks, and access to healthcare services, policymakers, employers, and stakeholders can promote a more fulfilling and dignified retirement for all.